Prof. Zenon Jagodziński (in memoriam) - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1999)
Professor Zenon Jagodziński was born in Samcieszynek, district Bydgoszcz, on April 5, 1913. He began his study at the Faculty of Architecture of the Technical University of Lvov in 1934. Four years later, he moved to Warsaw, when he specialised in radio engineering at the Technical University of Warsaw.